Exploration of Engineered Diode Current-Voltage Convergence for Maximum Power Point Tracking in Single-Axis Solar Tracker Systems. - Novita Asma Ilahi; Afrizal Abdi Musyafiq; Fadhillah Hazrina (Politeknik Piksi Ganesha Indonesia, 2025)
Indonesia, situated in the tropics, possesses optimal solar irradiation potential, positioning it as an ideal location for the deployment of photovoltaic (PV) energy systems. Given the escalating electricity demand driven by demographic expansion and technological advancements, harnessing solar panels as a viable alternative energy source is crucial. Nevertheless, static PV installations frequently yield suboptimal power absorption. This research, titled